Comparative analysis of cholesterol sensitivity of Kir channels: role of the CD loop - Rosenhouse-Dantsker, Avia (2010)
Kir channels are important in setting the resting membrane potential and modulating membrane excitability. A common feature of Kir2 channels and several other ion channels that has emerged in recent years is that they are regulated by cholesterol, a major lipid component of the plasma membrane whose excess is associated with multiple pathological conditions. Yet, the mechanism by which cholesterol affects channel function is not clear. We have recently shown that the sensitivity of Kir2 channels to cholesterol depends on residues in the CD loop of the cytosolic domain of the channels with one of the mutations, L222I, abrogating cholesterol sensitivity of the channels completely. Here we show that in addition to Kir2 channels, members of other Kir subfamilies are also regulated by cholesterol. Interestingly, while similarly to Kir2 channels, several Kir channels, Kir1.1, Kir4.1 and Kir6.2Δ36 were suppressed by an increase in membrane cholesterol, the function of Kir3.4* and Kir7.1 was enhanced following cholesterol enrichment. Furthermore, we show that independent of the impact of cholesterol on channel function, mutating residues in the corresponding positions of the CD loop in Kir2.1 and Kir3.4*, inhibits cholesterol sensitivity of Kir channels, thus extending the critical role of the CD loop beyond Kir2 channels.